Evaluation of sticky traps for adult Aedes mosquitoes in Malaysia: a potential monitoring and surveillance tool for the efficacy of control strategies. Issue 2 (10th November 2017) - Roslan, Muhammad Aidil; Ngui, Romano; Vythilingam, Indra; Sulaiman, Wan Yusoff Wan
ABSTRACT: The present study compared the performance of sticky traps in order to identify the most effective and practical trap for capturing Aedes aegypti and Aedes albopictus mosquitoes. Three phases were conducted in the study, with Phase 1 evaluating the five prototypes (Models A, B, C, D, and E) of sticky trap release‐and‐recapture using two groups of mosquito release numbers (five and 50) that were released in each replicate. Similarly, Phase 2 compared the performance between Model E and the classical ovitrap that had been modified (sticky ovitrap), using five and 50 mosquito release numbers. Further assessment of both traps was carried out in Phase 3, in which both traps were installed in nine sampling grids. Results from Phase 1 showed that Model E was the trap that recaptured higher numbers of mosquitoes when compared to Models A, B, C, and D. Further assessment between Model E and the modified sticky ovitrap (known as Model F) found that Model F outperformed Model E in both Phases 2 and 3. Thus, Model F was selected as the most effective and practical sticky trap, which could serve as an alternative tool for monitoring and controlling dengue vectors in Malaysia.